2010
DOI: 10.3758/s13421-010-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

Working memory capacity modulates task performance but has little influence on task choice

Abstract: Variation in the ability to maintain internal goals while resolving competition from multiple information streams has been related to individual differences in working memory capacity (WMC). In a multitask environment, task choice and task performance are influenced by internal goals, prior behavior within the environment, and the availability of relevant and irrelevant information in the environment. Using the voluntary task-switching procedure, task performance, as measured by switch costs, was related to WM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 55 publications
4
39
1
Order By: Relevance
“…Increased capacity could be assumed to lead to either more switching overall (as resources are less constrained) or more frequent switching at more opportune times (increased exploitation). However the former has failed to accumulate much evidence in voluntary task switching experiments, at least related to WM capacity (Butler, Arrington, & Weywadt, 2011). The latter has gone completely unexamined.…”
Section: Individual Differences In Executive Attentionmentioning
confidence: 99%
“…Increased capacity could be assumed to lead to either more switching overall (as resources are less constrained) or more frequent switching at more opportune times (increased exploitation). However the former has failed to accumulate much evidence in voluntary task switching experiments, at least related to WM capacity (Butler, Arrington, & Weywadt, 2011). The latter has gone completely unexamined.…”
Section: Individual Differences In Executive Attentionmentioning
confidence: 99%
“…Separating task choice from task execution allows us to disentangle the participants’ global task intentions from their specific actions. Different studies have provided evidence that these two reflect related yet dissociable processes (Mayr and Bell, 2006; Lien and Ruthruff, 2008; Arrington and Yates, 2009; Yeung, 2010; Butler et al, 2011; Orr and Weissman, 2011; Poljac et al, 2012). Specifically, while we know that task choice and task execution are sensitive to similar influences (Lien and Ruthruff, 2008; Yeung, 2010; Orr and Weissman, 2011), we also know that the expression of the behavioral costs related to task choice and those related to task execution differ.…”
Section: Intentional and Motor Control In Asdmentioning
confidence: 99%
“…We refer to intentional control as a specific subset of cognitive control processes that biases the choice of our behavioral goals and hence further facilitates selection and monitoring of goal-directed actions (cf. Mayr and Bell, 2006; Butler et al, 2011). We will also reflect on findings about cognitive control mechanisms across different age groups.…”
Section: Introduction To Autismmentioning
confidence: 99%
“…Second, recent studies have shown that switch costs in VTS are more likely to reflect cognitive control than switch costs observed in traditional task-switching procedures (e.g., Liefooghe et al, 2009, 2010; but see Yeung, 2010). Third, some studies have found evidence that the selection component and the execution component in VTS are underlain by distinct sets of processes and are taxing different sets of control processes (see also Arrington and Yates, 2009; Butler et al, 2011). Thus, besides a switch cost, this procedure also offers an additional index of choice behavior and thus of cognitive flexibility.…”
Section: Introductionmentioning
confidence: 99%